Analisis Bentuk Dari Nilai-Nilai Pendidikan Pada Cerita Rakyat Di Pariaman Sumatera Barat - Husna Maizar; Yusni Khairul Amri (Keguruan, 2022)
This study aims to analyze what educational values are contained in the folklore of the Origin of Maninjau Lake, Pariman, West Sumatra. The place of research is only focused on texts or fairy tale books so the place of research is in the library to find reference books from research results. As for facilitating the process of conducting research, starting from August 2022 to October 2022. The source of research data used in this research is from secondary data, namely from story books and relevant supporting journals. As for the method of data analysis in this study using a network analysis model, namely by suggesting the analysis process with the three components of the analysis are intertwined and carried out continuously. Based on the analysis of research data in the previous chapter, it can be concluded that in this study educational values were found in the story of the Origin of Lake Maninjau including educational values, religious values, moral values, social values and cultural values. The value of education in the form of religious values is more prevalent in the story of the Origin of Lake Maninjau, around 40%.